The Geopolitical Dimensions of the Iranian-Emirati Dispute over the Islands in the Persian Gulf - Aziz, Saddam Badr (Journal of Tikrit University for Humanities, 2024)
This study aims at the geopolitical dimensions of the Iranian-Emirati conflict over the three islands in the Arabian Gulf. This paper consists of four sections. The first section represents the general geographical characteristics of the study area ((natural and human)). The second section is concerned with evaluating the geological situation of the UAE islands before the British withdrawal from the Gulf and after the British withdrawal From the Gulf, as for the third section, it is represented by the geopolitical importance of the three Emirates islands in terms of strategy, economics and geopolitics. The fourth section is represented by the position of the three Arab islands in the policies of international and regional powers, which were represented by Iran, Britain and America.